2012
DOI: 10.1177/0885328212457097
|View full text |Cite
|
Sign up to set email alerts
|

Properties and osteoblast cytocompatibility of self-curing acrylic cements modified by glass fillers

Abstract: Materials filled with a silicate glass (MSi) and a borate glass (MB) were developed and compared in terms of their in vitro behavior. The effect of filler composition and concentration (0, 30, 40 and 50 wt%) on the curing parameters, residual monomer, water uptake, weight loss, bioactivity, mechanical properties (bending and compression) and osteoblast cytocompatibility was evaluated. The addition of bioactive glass filler significantly improved the cements curing parameters and the mechanical properties. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…The use of silicate based bioactive glasses is reported to promote osteoblast adhesion and proliferation. 28 In our study, MTS assay showed that DPSC proliferation initially increased (up to day 5) for all composition studied. However, it was compromised at day 9 when composites contained high contents of nBG ( Figure 12).…”
Section: Properties Of Composites After Sbf Conditioningsupporting
confidence: 56%
“…The use of silicate based bioactive glasses is reported to promote osteoblast adhesion and proliferation. 28 In our study, MTS assay showed that DPSC proliferation initially increased (up to day 5) for all composition studied. However, it was compromised at day 9 when composites contained high contents of nBG ( Figure 12).…”
Section: Properties Of Composites After Sbf Conditioningsupporting
confidence: 56%
“…High water uptake can compromise the mechanical properties of cement (Lopes et al, ), and therefore this value was monitored. The weights of the composites increased over time in solution as more liquid entered them.…”
Section: Discussionmentioning
confidence: 99%
“…After soaking for 0, 1, 3, 7, or 21 days, specimens were taken out of solution, rinsed with deionized water, blotted dry, and weighed. Water uptake (% weight increase) was calculated as described by Lopes et al (). Specimens were dried in an oven at 90°C for 1 day to ensure that no water remained (Cui et al, ; Fu, Rahaman, Fu, & Liu, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating such fillers into PMMA cement by mechanical mixing has also achieved the purpose of improved bone bonding. 79 However, in some cases, this method still faces challenges in its details. For example, the formation of apatite was restricted to spots where the bioactive particles could be exposed to body fluid, and acquiring a better performance for affinity and osteoconductivity required an increase in the content of glass bead filler to 70 mass%.…”
Section: Introductionmentioning
confidence: 99%